Teknik Operasional Pengelolaan Sampah di Kawasan BTN Rajawali Residense Kota Kendari: (Studi Kasus Kawasan BTN Rajawali Residence, Kelurahan Baruga, Kecamatan Baruga, Kota Kendari) - Sadikin, Ali; Eka Pratiwi, Yunita; Ndibale, Wa (Universitas Muhammadiyah Kendari, 2025)
Waste can cause problems that until now have not been resolved in waste management. Waste management that has not been implemented optimally can later affect the condition of the surrounding environment. Waste that has not been managed properly and the increasing rate of waste generation can reflect the existence of a waste management system that has not been carried out effectively and still requires a structured waste management method.The aim of this research is waste management, which collects, transports and disposes of waste, now will change to a new paradigm through management at the place of origin or waste management site in the form of a Waste Processing Facility (TPS) using the Reduce, Reuse, Recycle (3R) Method.The results of this study indicate that the amount of waste generated in the Rajawali Reseidence housing complex is a waste weight of 0.025 kg/person/day and a waste volume of 2.934 liters/person/day. The composition of waste produced in the BTN Rajawali Residence housing complex is, plastic waste of 0.814 kg/person/day, wood and garden waste of 0.151 kg/person/day, B3 waste of 0.317 kg/person/day, food waste of 3.904 kg/person/day, paper waste of 0.489 kg/person/day, textile waste of 0.000335 kg/person/day, metal waste of 0.0097 kg/person/day and glass waste of 0.107 kg/person/day. Evaluation of operational techniques for waste management in BTN Rajawali Residence housing based on SNI 19-2454-2002, namely, the container is appropriate but individual containers must be improved again, Collection is appropriate (collection is carried out routinely), transportation is appropriate (TPS waste is transported to TPA), waste transfer requires an effective schedule and good route, processing is not appropriate (must be more comprehensive for both organic and inorganic waste), final disposal (TPA is not explained in detail, but there are opportunities for development to increase efficiency and reduce environmental impact). In general, this system has met the standards set for operational aspects. However, there are some that need to be improved.